Anchoring geometry is a significant factor in determining the direction of kinesin-14 motility on microtubules - Masahiko Yamagishi; Rieko Sumiyoshi; Douglas R. Drummond; Junichiro Yajima (Scientific Reports, 2022)
Abstract Kinesin-14 microtubule-based motors have an N-terminal tail attaching the catalytic core to its load and usually move towards microtubule minus ends, whilst most other kinesins have a C-terminal tail and move towards plus ends. Loss of conserved sequences external to the motor domain causes kinesin-14 to switch to plus-end motility, showing that an N-terminal attachment is compatible with plus-end motility. However, there has been no systematic study on the role of attachment position in minus-end motility. We therefore examined the motility of monomeric kinesin-14s differing only in their attachment point. We find that a C-terminal attachment point causes kinesin-14s to become plus-end-directed, with microtubule corkscrewing rotation direction and pitch in motility assays similar to that of kinesin-1, suggesting that both C-kinesin kinesins-14 and N-kinesin kinesin-1 share a highly conserved catalytic core function with an intrinsic plus-end bias. Thus, an N-terminal attachment is one of the requirements for minus-end motility in kinesin-14.